Предпоследний герой: Роман / А. В. Литвинова, С. В. Литвинов - Литвинова Анна Витальевна (Русский стиль, 2003)
Экземпляры: (20211019) / Инвентарный номер: 29732 / Цена: 56.00 / Сис.шифр: 84(2=411.2)6 / Авт.знак: Л 64 / ГРНТИ: 17 / ББК: 84(2=411.2)6